Shackled Love: The Lived Experience of Mothers Behind Bars from Pregnancy to Parenthood FROM PREGNANCY TO PARENTHOOD - Elyza Kimberly Y. Villarante; Nicco Inri B. Palermo; Stephanie P. Miñoza; Sonny Boy B. Bombio; Devianne Jane Esmas Daiz (Aloha International Journal of Health Advancement (AIJHA), 2019)
This study explored the lived experience of pregnant mothers behind bars. Affixed by the philosophy of Hans-Georg on hermeneutic phenomenology, individual semi-structured interviews were done with nine (9) informants. After transcribed interviews, reflection and interpretation were done with Max Van Manen’s four lifeworlds. Six major themes emerged namely: (1) “Yearning Inmate” with subthemes: (a) “Corporeal Desire”, and (b) “Familial Longingness”; (2) “The Long Journey Ahead” with subthemes: (a) “Mother’s Preparation”, and (b) “Prisoner’s Delivery Experience”; (3) “The Value of Time”; (4) “The Separation” with subthemes: (a) “Sadness vs. Security”, and (b) “Estranged”; (5) “To Light A Fire”; (6) “Somehow, Sometime, Someday” with subthemes: (a) “Hope: For Myself”, and (b) “Hope: For my baby”. Findings revealed how being a mother behind bars is no easy situation. They have several preparations to make before giving birth and just a few days after delivery, the baby is taken away. Over time, the child will no longer recognize them and so they try to mend the broken relationship they have. Keywords: Motherhood, Imprisoned, Incarcerated, Interpretive phenomenology, Hermeneutics